The Nairobi Pork Value Chain: Mapping and Assessment of Governance, Challenges, and Food Safety Issues - Murungi, Maurice K.; Muloi, Dishon M.; Muinde, Patrick; Githigia, Samuel Maina; Akoko, James; Fèvre, Eric M.; Rushton, Jonathan; Alarcon, Pablo (Frontiers in Veterinary Science, 2021)
The Nairobi pork food system is a growing livestock sub sector as a source of food and livelihood to its inhabitants. The study aimed to map the Nairobi pork value chains, assess their governance, challenges and their impact on food safety risks and management practices. Qualitative data were collected in seven focus group discussion and 10 key informants’ interviews on animal and product flows, stakeholders’ interactions, perceptions on system governance and challenges, and on their potential impact on food safety management. Quantitative data was obtained to show the importance of flows, business operations and market share. Thematic analysis was conducted to identify themes that provide understanding on the governance, challenges and food safety practices in each profile. The predominant chains identified were 1) The ‘large integrated company’ profile which accounted for 83.6% of pork marketed through abattoirs, and was based on a well-structured supply system, with owned farms (representing 50% of their supply), contract farms and semi-contract farms and 2) Local independent abattoirs which are privately owned small-scale production supplied mainly (70%) by small farmers from the immediate neighbouring areas. The main governance themes included; i) Inadequate/lack of enforcement of existing regulation ii) Negative effect of devolution system of governance iii) Pig traders’ dominance iii) Lack of association at all system nodes, and iv) Male dominance across the pig system. The main challenges reported included; i) Lack of capital to upgrade ii) Poor infrastructure iii) Pig shortage iv) Too much regulation v) Lack of training vi) Diseases v) Lack of knowledge vi) Unfair competition. Food safety themes were associated with i) Inadequate slaughter facilities thus forcing traders/farmers to undertake home slaughter ii) Lack of knowledge on disease management iii) Lack of training on hygienic practices in the slaughterhouse and iv) Lack/insufficient capital to purchase equipment’s to ensure proper hygiene e.g. boilers. The study provides insights on the structure of the pork system supplying Nairobi, the governance issues important to the stakeholders, challenges and food safety issues. The framework obtain can be used by policy makers and researchers to investigate and develop industry and for food safety and disease control programmes.